2015
DOI: 10.1108/jiabr-03-2013-0005
|View full text |Cite
|
Sign up to set email alerts
|

The quality of earnings in Shariah-compliant companies: evidence from Malaysia

Abstract: Purpose – The purpose of this study is to examine the quality of reported earnings in the corporate reports of Shariah-compliant companies listed on Bursa Malaysia. Design/methodology/approach – This study hypothesises that companies with Shariah compliance status have higher quality of earnings because of greater demand for and supply of high-quality financial reports. The quality of reported earnings is measured using the cross-section… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
59
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(67 citation statements)
references
References 64 publications
8
59
0
Order By: Relevance
“…Columns 2 and 3 provide an interesting observation, i.e., that non-compliant firms tend to record a greater level of reduction relative to their compliant counterparts. The findings also suggest that compliant firms tend to be more sustainable in nature, as these firms tend to have a higher degree of earnings quality [48], and hence, are less susceptible to shocks in equity values, as evidenced by significantly lower levels of reduction in book leverage ratios. Thus, non-compliant firms are more focused on redeeming debt instruments to lower the book debt ratio.…”
Section: Partial Adjustment Of Leverage In Response To Shocks In Equimentioning
confidence: 83%
“…Columns 2 and 3 provide an interesting observation, i.e., that non-compliant firms tend to record a greater level of reduction relative to their compliant counterparts. The findings also suggest that compliant firms tend to be more sustainable in nature, as these firms tend to have a higher degree of earnings quality [48], and hence, are less susceptible to shocks in equity values, as evidenced by significantly lower levels of reduction in book leverage ratios. Thus, non-compliant firms are more focused on redeeming debt instruments to lower the book debt ratio.…”
Section: Partial Adjustment Of Leverage In Response To Shocks In Equimentioning
confidence: 83%
“…Such companies are expected to adhere to Islamic or Shariah values which are favoured by the society. Shariah-compliant companies are thus subjected to greater scrutiny by regulators and other stakeholders (Wan Ismail et al, 2015). Taking this as a possible way to gauge companies, this study aims to examine the effect a company's reputation may have in influencing the management into engaging with earnings management practices.…”
Section: Earning Management and Reputationmentioning
confidence: 99%
“…Ibrahim et al (2015), for example, found that companies offering Islamic products and services tend to practise sustainability reporting, which are also less involved in earnings management behaviour. Based on the robust evidence, Wan Ismail, Kamarudin and Sarman (2015) noted that Shariah-compliant companies have significantly higher earnings quality. Nonetheless, there are studies which claim that companies that are significantly influenced by religion, specifically Islam, also performed unethical conducts including earnings management behaviour (e.g., Dyreng, Mayew, & Williams, 2012;Alkdai & Hanefah, 2012;Hamdi & Zarai, 2012;Farooq & AbdelBari, 2015;Alsaadi, Ebrahim, & Jaafar, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This journal is a member of and subscribes to the principles of the Committee on Publication Ethics (COPE) (Mohamed Adil & Mohd-Sanusi, 2013;Wan Ismail, Kamarudin, & Sarman, 2015).…”
Section: Introductionmentioning
confidence: 99%